Benign thoracic pain. - Bruckner, F E (1987)
Seventy-three patients with mid-dorsal and/or unilateral chest pain seen consecutively in the rheumatology clinic by a single clinician over a three-year period were studied, after exclusion of visceral disease. The majority were young women. The pain was dull and continuous, was aggravated by coughing and sneezing and relieved by rest. There was frequently tenderness over the thoracic spine (T4-5) and an adjacent rib, and pain at extremes of thoracic spinal movement in one or two directions was invariable. Cutaneous hyperaesthesia in a radicular distribution was found in 16.4%, but there were no other neurological abnormalities. This clinical picture is probably the result of a thoracic disc prolapse, though confirmation by myelography was not thought to be ethically justified. The condition settled in most of the patients following manipulative treatment and advice on back care. No patient developed spinal cord compression. It is concluded that this is a common benign condition which deserves wider recognition.